The Course «Comparative Pedagogics» in Professional Preparation of the Future Primary School Teachers - Kryshchuk, Bohdan (Pedagogical Discourse, 2014)
The author of the article attempted to reveal the content of the course «Comparative Pedagogics» in professional formation of the future primary school teacher. On the basis of the analysis of the textbooks and manuals on comparative pedagogics, regulatory and legal framework of specialist’s preparation, the structure of the course «Comparative Pedagogics» for the future teachers is shown. The author indicated the topicality and the degree of research of the problem, the role of comparative pedagogics in professional formation of a pedagogue. The structure of the study of the discipline «Comparative Pedagogics» in higher pedagogical educational establishment has been offered. It consists of 8 contextual modules, namely: comparative pedagogics as a science; methods of comparative pedagogics; pre-school education in different educational systems; comparative analysis of the systems of general secondary education; development of professional-technical education in the leading countries of the world; development of higher education in different countries; the ways of rising effectiveness of education in the leading countries of the world and in Ukraine; preparation of the teacher from the point of view of comparative pedagogics. The knowledge, which students should possess as a result of study of «Comparative Pedagogics», as well as the methods of teaching and control for the educational-cognitive activity, have been mentioned.